Infectious spleen and kidney necrosis virus induces the reactive oxidative species/Nrf2-mediated oxidative stress response for the regulation of mitochondrion-mediated Bax/Bak cell death signals in GF-1 cells - Chen, Pin-Han; Hsueh, Tsai-Ching; Hong, Jiann-Ruey (Frontiers in Microbiology, 2022)
Infectious spleen and kidney necrosis virus (ISKNV) infections can trigger host cell death and are correlated with viral replication; however, they have rarely been considered in terms of the host organelle involvement. In the present study, we demonstrated that ISKNV triggered an oxidative stress signal in the Nrf2-mediated oxidative stress response and induced stress signals for Bax/Bak-mediated host cell death in fish GF-1 cells. The results showed that after ISKNV infection, the levels of reactive oxidative species (ROS) increased by 60–80% from day 3 to day 5, as assessed by an H2DCFDA assay for tracing hydrogen peroxide (H2O2), which was correlated with up to a one-fold change in the fish GF-1 cells. Furthermore, we found that ISKNV infection induced Nrf2-mediated ROS stress signals from D1 to D5, which were correlated with the upregulation of antioxidant enzymes, such as catalase, SOD1, and SOD2; these effects were blocked by the antioxidants GSH and NAC. By analyzing Nrf2-mediated ROS stress signals for cell death regulation via an apoptotic assay, we found that treatment with antioxidants reduced annexin-V-positive signals by 10% (GSH) to 15% (NAC); moreover, necrotic-positive signals were reduced by 6% (GSH) and 32% (NAC) at day 5 (D5) in GF-1 cells, as indicated by PI staining. Furthermore, we found that Nrf2-mediated ROS stress regulated mitochondrion-mediated Bax/Bak death signals at D3 and D5; this was effectively blocked by antioxidant treatment in the GF-1 cells, as demonstrated by a JC1 assay (ΔΨm) and western blot analysis. In addition, we found that downstream signals for caspase-9 and -3 activation were apparently blocked by antioxidant treatment at D3 and D5. Finally, we found that treatment with GSH and NAC reduced major capsid protein (MCP) expression and virus titer (TCID50%) by up to 15-fold at D5 in GF-1 cells. Thus, our data suggest that ISKNV can induce ROS production, which triggers Nrf2-mediated stress signals. Then, these stress signals can regulate mitochondrion-mediated Bax/Bak apoptotic signaling, which is connected to downstream caspase-9 and -3 activation. If ISKNV-induced Nrf2-mediated stress signaling is blocked, then the antioxidants GSH and NAC can also suppress apoptotic signals or reduce viral replication. These findings may provide insights into the control and treatment of double-stranded DNA viruses.